The Implementation of Word Find Game to Improve Students’ English Vocabulary - Ratna Ratna; Nasriandi Nasriandi; Jusriati Jusriati (Edumaspul: Jurnal Pendidikan, 2023)
This research is Quasi Experimental Research. The objective of this research is to investigate the process of improving students’ English vocabulary by using word find game. The respondents in this research are the eleventh grade students of MAN Bantaeng, consist of 30 students which divided into two group of class where 15 students from MIA 2 as experiment class and 15 students from MIA 1 as a control class. In collecting data, this research used pre-test and post-test. Data calculation using SPSS v.20. The independent variable of this research is word find game and the dependent variable of this research is students’ english vocabulary. This research used random sampling technique. The results of the research showed that score test on pre-test in experiment class was 74.33 and score test pre-test in control class was 65.00. The score post-test in experiment class was 92.67 and score post-test in control class was 76.73. The results of the research showed that the implementation of word find game can increase students' English vocabulary.